The Role of Early Childhood Education and Community Participation in Fostering Waste Management Awareness Among Young Children in Palembang City - Cintantya Andhita Dara Kirana; Surya Tri Esthi Wira Hutama; Hendry Natanael Gumano; Chrisna Trie Hadi Permana (Kolaborasi : Jurnal Administrasi Publik, 2026)
Regulations and policies of Law of the Republic of Indonesia Number 18 of 2008 and its derivatives on Waste Management have ushered in a more comprehensive and integrated waste management system in Palembang City from upstream to downstream which includes waste reduction and processing activities. However, there are problems in maintaining the environment sustainably. Sustainable environmental development needs to optimize waste management from upstream (reduce, reuse, recycle) to downstream. This study aims to evaluate the extent and quality of waste management awareness among early childhood education students in Palembang City, and to assess the role of school-based curricula and parental participation in shaping that awareness. Specifically, it asks: (1) To what degree do students in Palembang understand core waste management concepts (sorting, reduction, recycling, composting)? (2) How do institutional and parental factors mediate or constrain that understanding? (3) What does the Paulo Freire’s empowerment framework reveal about the transformative potential and limitations of current pedagogical practices? The research method used is a mix method, namely by combining quantitative and qualitative approaches. Data sources are from the results of interviews, observations and documentation studies. The results of the study revealed that waste management activities that have been taught by early childhood education teachers cannot all be understood by each student due to the age limitation to understand waste materials and their management, so it is necessary to invite parents to be involved in children's waste management activities and provide education related to practices that can be done at home.